Impulse and Momentum Linear Teaching Materials with Al-Quran Verses to Practice Problem Solving Skills of Students: Practicality and Effectiveness - Azhary, Yayan; Mastuang, Mastuang; Dewantara, Dewi (Universitas Nurul Huda, 2022)
This study aims to describe the practicality and effectiveness of impulse and linear momentum teaching materials containing verses of the Koran to train students' problem-solving skills. This research is research and development (R&D) using the ADDIE model and tested on 12 students of class X MIPA 1 MAN 2 Banjarmasin. Data collection was obtained through a questionnaire instrument for student responses, and a test of students' cognitive learning outcomes and analyzed descriptively quantitatively. The results showed that: (1) teaching materials obtained a fairly practical category with a score of 2.48, (2) teaching materials obtained in the less effective category the N-gain value is 0.13 with a low category. It was concluded that the teaching materials were quite practical but not effective for practicing problem solving skills